Mai i te Ao Rangatahi ki te Ao Pakeke Ka Awatea: A Study of Māori Student Success Revisited. (March 2021) - Duckworth, Fiona; Gibson, Marie; Macfarlane, Sonja; Macfarlane, Angus
This article responds to the paucity of literature on Māori success and presents data from follow-up interviews with eight Māori young adults (pakeke), 6 years after they participated as secondary students (rangatahi) in an initial study titled Ka Awatea: An Iwi Case Study of Māori Students ' Success in 2014. Emerging outcomes reveal the central role of Māori culture and identity in their transition to adulthood. Secondary schooling nurtured their inner confidence and capacity to achieve, but did not play a significant role in development of positive Māori identity and cultural efficacy. However, as school-leavers approaching adulthood, they drew on their cultural efficacy and cultural assets, predominantly acquired from whānau, to navigate dominant culture environments. In doing so, they demonstrate that traditional Māori developmental paths have contemporary relevance, and that their roles—as cultural bearers, passing on the gifts of their ancestors—are fundamental to their aspirations and achievements.